Notes on Omalonyx - Pat Watt Herman; Dee Saunders Dundee (Hello World!, 1967)
The habits of Omalonyx are incompletely known. These strange-looking Succineids are known from South America (Brasil, Argentina, Paraguay, Uruguay, Bolivia, Venezuela) and the Lesser Antilles (Dominica, Guadeloupe, Trinidad). In this paper we are reporting their presence in Ecuador, St. Lucia and Antigua.